If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 17) = 10x + -2 Reorder the terms: 2(17 + x) = 10x + -2 (17 * 2 + x * 2) = 10x + -2 (34 + 2x) = 10x + -2 Reorder the terms: 34 + 2x = -2 + 10x Solving 34 + 2x = -2 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 34 + 2x + -10x = -2 + 10x + -10x Combine like terms: 2x + -10x = -8x 34 + -8x = -2 + 10x + -10x Combine like terms: 10x + -10x = 0 34 + -8x = -2 + 0 34 + -8x = -2 Add '-34' to each side of the equation. 34 + -34 + -8x = -2 + -34 Combine like terms: 34 + -34 = 0 0 + -8x = -2 + -34 -8x = -2 + -34 Combine like terms: -2 + -34 = -36 -8x = -36 Divide each side by '-8'. x = 4.5 Simplifying x = 4.5
| Y=1-1.5x | | 2=n-2/7 | | 8+4x=13-1x | | 8x+13-11x=7 | | ×/-5=-8 | | -10y=x^2+8x+4 | | (3n-4)(5n+2)=0 | | y=-x^2+14x-45 | | 5.99+1.99x=20.99 | | 11.3x+7=4.6x+22.41 | | -5.6=y | | (3-i)-(2+6i)= | | 8x+3-7=12 | | Y-1=2(x-3/2) | | 2.6x+78=5.1x+18 | | 7x=9x-9 | | 4+6x=7x-7 | | 5x+9=10x-7 | | 5(x+4)-x=32 | | (4a+3)(a-1)=0 | | 18y=29x-52 | | -16.28=29.3-8.6y | | Y-1=2(x-2/3) | | 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 |